Artificial Intelligence in Governance: The State of Facial Recognition Technology in Canada - Prasad Adhhikari, Achyut (Policy & Governance Review, 2025)
Innovation in public service delivery can help the rapid transformation of society into a post-COVID era. In addition to minimizing administrative hassles, efficiently using Artificial Intelligence (AI) can protect citizens from unwanted behaviors. AI broadly denotes the efficiency of computers in replicating human intelligence, such as identifying different patterns and making predictions and decisions. AI encompasses numerous techniques, and machine learning is one of the most widely used. Machine learning is a method of deploying large datasets to make predictions that improve over time with more data. By 2030, Canada aims to have one of the most robust national AI ecosystems in the world, founded upon scientific excellence, high-quality training, deep talent pools, public-private collaboration, and their strong value of advancing AI technologies to bring positive social, economic, and environmental benefits for people and the planet. This study intended to assess the overall situation of AI in governance and policy compliance. I found that the country relies on patchwork and faces numerous legal and practical issues owing to the absence of an umbrella policy and organization. This research also proposes ideas to enhance governance to improve biometric data protection, legal frameworks, and quality standards for collecting biometric data based on the FRT. This study is based on focus group discussions, policy papers of the government of Canada, and many other literature and research articles.